Observasi dan Identifikasi Virus yang Menginfeksi Bawang Merah di Jawa - Tuty Arisuryanti; Budi Setiadi Daryono; Sedyo Hartono; Anak Agung Gde Raka Swastika (Universitas Gadjah Mada, 2008)
This study was conducted to observe and identify viruses from infected shallots in several shallot planting center. The observation was done in eight areas of three provinces (Yogyakarta, Central Java, and East Java). Leaves from shallot plants and shallot germination showing virus symptoms were examined. The leaves were then investigated to identify viruses infecting shallots using Enzyme-Linked Immunosorbent Assay (ELISA). The result revealed that the type of virus symptoms infecting the shallots was a mozaic symptom with yellow strips. The ELISA analysis showed that Tawangmangu Biru shallot cultivar plants sampled from Blumbang, Tawangmangu (Central Java) and Philiphine Bima shallot cultivar seeds collected from Srigading, Sanden, Bantul (Yogyakarta) were positively infected by Onion Yellow Dwarf Virus (OYDV). The result also revealed that Biru, Kuning Tablet, Lokal Tawangmangu, and Bima Curut shallot cultivars had the potency to be virus resistant plants and could be considered as candidates for breeding program.